Predictors of vaginal delivery following balloon catheter for labor induction in women with one previous cesarean - Kaidong Ma; Ming Yang; Xiaoling Feng; Liyuan Liu; Liangliang Li; Yunxiu Li (BMC, 2023)
Abstract Background The aim of this study was to estimate predictors for vaginal birth following balloon catheter induction of labor (IOL) in women with one previous cesarean section (CS) and an unfavorable cervix. Methods This 4-year retrospective cohort study was conducted in Longhua District Central Hospital in Shenzhen China, between January 2015 and December 2018. Patients with one previous CS and a current singleton-term pregnancy who underwent balloon catheter cervical ripening and IOL were enrolled. Univariate analysis was used to identify predictive factors associated with vaginal birth after cesarean section (VBAC). Binary logistic regression was further used to identify which factors were independently associated with the outcome measure. The primary outcome was VBAC, which was a successful trial of labor after cesarean delivery (TOLAC) following IOL. Results A total of 69.57% (208/299) of the women who planned for IOL had VBAC. In the final binary logistic regression equation, lower fetal weight (< 4000 g) (odds ratio [OR]5.26; 95% confidence interval [CI] 2.09,13.27), lower body mass index (BMI,<30 kg/m2) (OR 2.27; CI 1.21, 4.26), Bishop score after cervical ripening > 6 (OR 1.94; CI 1.37, 2.76) remained independently associated with an increased chance of VBAC. Conclusions The influencing factors of VBAC following IOL were fetal weight, BMI, and Bishop score after cervical ripening. Adequate individualized management and assessment of the IOL may help improve the VBAC rate.